2001
DOI: 10.1111/j.1572-0241.2001.05259.x
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological survey of constipation in Canada: definitions, rates, demographics, and predictors of health care seeking

Abstract: Functional constipation and related health care seeking are common in the Canadian population and are strongly determined by the definition used. The Rome II criteria for this disorder seem to be satisfactory, but modifications may be considered to allow for constipated subjects taking laxatives and to increase the number of qualifying symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
269
3
29

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 405 publications
(331 citation statements)
references
References 10 publications
28
269
3
29
Order By: Relevance
“…The prevalence of Rome I-defined functional constipation in the present group was 26.2%. A similar prevalence by these criteria has been reported in Canadian (21.0%) (Pare et al, 2001) and Spanish (28.6%) (Garrigues et al, 2004) women, whereas a somewhat smaller ratio was seen in elderly Singaporean women (10.5%) (Wong et al, 1999).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The prevalence of Rome I-defined functional constipation in the present group was 26.2%. A similar prevalence by these criteria has been reported in Canadian (21.0%) (Pare et al, 2001) and Spanish (28.6%) (Garrigues et al, 2004) women, whereas a somewhat smaller ratio was seen in elderly Singaporean women (10.5%) (Wong et al, 1999).…”
Section: Discussionsupporting
confidence: 82%
“…We used the definition of functional constipation recommended by an international workshop on the management of constipation (Rome I criteria) (Whitehead et al, 1991). Although the Rome I criteria were modified in 1999 to the Rome II criteria (Thompson et al, 1999), epidemiologic studies have consistently shown that the latter may be too restrictive for the diagnosis of constipation (Pare et al, 2001;Garrigues et al, 2004), and we therefore used the former. The following four questions were used to assess Rome I-defined functional constipation: (1) Do you strain during a bowel movement?…”
Section: Constipationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall (counting both reported and observed) mean bowel motions per week was 4.32 (SD=2.37) with no significant difference in the distribution between the male and female. 62% of subjects had laxatives ordered on a [3,6,[10][11][12] and physical symptoms [6,11]. Advanced age also predisposes to chronic constipation with an abrupt rise in prevalence after the age of 70 years [6].…”
Section: Resultsmentioning
confidence: 99%
“…The term constipation may be interpreted differently by patients as compared to physicians. While physicians often equate constipation with less than three bowel movements per week [1,2], patients would consider other factors like urge, straining, feelings of incomplete emptying and stool consistency [3,4]. Here in Kingston, Ontario, a therapeutic protocol for chronic constipation had been used in a long-term care facility amongst the residents.…”
Section: Problem Of Chronic Constipationmentioning
confidence: 99%